Globally framed para f-structure manifolds - Al-Aqeel, A. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this note, the definition of a globally framed para f-structure manifold is given. It is shown that an almost product structure, or a para contact structure, can be dafined, on a globally framed para f-structure man fold, depending on the number of the vector field in the characteristic equation.